Experimental Investigation on Dynamic Viscosity and Rheology of Water-Crude Oil Two Phases FlowBehavior at Different Water Volume Fractions - Abd Rasha, Mohammed; Nour, A. H.; Ahmad Ziad, Sulaiman (AJER, 2014)
Emulsionconsidered as a ruthless problem within the petroleum industry due to their various costly problems in terms of production loss and transport difficulties. In this study, the dynamic viscosity and rheological properties of water-oil two phase flow were investigated using emulsion and blending with lighter crude oil approaches at different water volume fractions. Water-in-oil emulsion stabilized by (1.5 vol.%) of Cocamide DEA was considered in the study. Two samples of crude oil were used: Heavy crude oil, and heavylight blended crude oil at (60-40) vol.%. The dynamic viscosity was determined by Brokfeild Rotational Digital Viscometer Model LV/DV-III. Factors that affect the emulsion rheologyical properties: temperature, rotational speed, shear rate, shear stress, and water volume fractionwas inspected.Results showed that the water-in-heavy oil emulsion approach resulted in reducing the viscosity of original crude oil about (14%) and characterized the Non-Newtonian shear thinning “pseudo-plastic” behavior. On the other hand, the second approach of blending with (40 vol.%) of lighter crude oil showed that the viscosity and the density were significantlyreduced to (93.6 %), and (5.7%) at 30 ͦ C, respectively. However, water-in- blended crude oil emulsion followed the same behavior of the original crude oil emulsion under the same factors and conditions. Finally, the rheology studies of both approaches showed that temperature, shear rate,and water volume fraction have a great impact on the viscosity behavior of water-oil two phase flow.